Hubungan Tingkat Pengetahuan terhadap Sikap Masyarakat dalam Mencegah Infeksi Jamur Kulit Pascabanjir di Matangkuli - Siti El Humairi Nuradenin Daulay; Wizar Putri Mellaratna; Wheny Utariningsih (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Flooding is one of the disasters that often occurs in Aceh Province. One of the areas in North Aceh Regency that is most frequently affected by flooding is the Matangkuli sub-district with an annual incidence of more than 10 times with a height of more than one meter. One of the impacts of flooding on public health is the occurrence of skin diseases caused by fungi. The purpose of this study was to determine the relationship between the level of knowledge and attitudes of the community to preventing fungal skin infections in Matangkuli District.The method used in this study is descriptive correlative using a cross sectional design. Sampling in this study used a cluster sampling technique with a sample of 92 respondents.Data analysis in this study used the Spearman correlation test. The results of this study, namely, 62% of respondents had a good level of knowledge of preventing post-flood skin fungal infections and a good attitude towards preventing post-flood skin fungal infections was found in 78.26% of respondents.This study also found a strong relationship between the level of knowledge and attitudes towards preventing fungal skin infections with a correlation coefficient (r-value) of 0.752 which indicates a strong relationship between knowledge and attitudes of the community in preventing post-flood fungal skin infections.